Comparative Analyses of Antibiotic Resistance Genes in Jejunum Microbiota of Pigs in Different Areas - Li, Yongxiang; Yang, Yuting; Ma, Li; Liu, Jianping; An, Qingcong; Zhang, Chunyong; Yin, Gefen; Cao, Zhenhui; Pan, Hongbin (Frontiers in Cellular and Infection Microbiology, 2022)
Antibiotic resistance genes (ARGs) are emerging environmental contaminants that threaten human and animal health. Intestinal microbiota may be an important ARGs repository, and intensive animal farming is a likely contributor to the environmental burden of ARGs. Using metagenomic sequencing, we investigated the structure, function, and drug resistance of the jejunal microbial community in Landrace (LA, Kunming), Saba (SB, Kunming), Dahe (DH, Qujing), and Diannan small-ear piglets (DS, Xishuangbanna) from different areas in Yunnan Province, China. Remarkable differences in jejunal microbial diversity among the different pig breeds, while the microbial composition of pig breeds in close areas tends to be similar. Functional analysis showed that there were abundant metabolic pathways and carbohydrate enzymes in all samples. In total, 32,487 ARGs were detected in all samples, which showed resistance to 38 categories of drugs. The abundance of ARGs in jejunum was not significantly different between LA and SB from the same area, but significantly different between DS, DH and LA or SB from different areas. Therefore, the abundance of ARGs was little affected by pig breeds and microorganism community structure, but it was closely related to geographical location. In addition, as a probiotic, Lactobacillus amylovorus is also an important ARGs producing bacterium. Our results revealed the antibiotic exposure and intestinal microbial resistance of farms in the study areas, which could provide basic knowledge and potential strategies for rational use of antibiotics and reducing the risk of ARGs transmission in animal husbandry.